Maternal, fetal, and perinatal outcomes of COVID-19-infected pregnancies in Saudi Arabia: a meta-analysis and systematic review - Ahmad Alwazzan (Italian Journal of Medicine)
The SARS-CoV-2 pandemic has been researched in various conditions to know the extent of its damage. During pregnancy, there is a placental exchange of blood between mother and fetus. This meta-analysis aimed to investigate the prevalence of maternal, fetal, and perinatal outcomes of COVID-19-positive pregnancy cases in Saudi Arabia. PubMed, Google Scholar, and Web of Science were searched for the period 2019-2024. Pregnancy cases only from Saudi Arabia and reverse transcription polymerase chain reaction confirmed COVID-19 positive were included. Women with any other diseases were excluded. Six studies were selected for meta-analysis with a total of 1065 COVID-19-infected pregnancies. Among the maternal conditions, preterm rupture of membrane (PROM) had the highest prevalence [odds ratio (OR)=4.21; 95% confidence interval (CI): 1.4-7]. Among fetal outcomes, the odds of postpartum anomalies were 4.8 (95% CI: 1.3-11). Intrapartum complications among perinatal outcomes were most likely to occur (OR=2.11; 95% CI: 120.9-125.1). No factual trend for a particular condition can be declared. PROM, postpartum, and intrapartum complications were more likely to occur in COVID-19-infected pregnancies.